Peran Industri Microstock Animasi dalam Mendorong Pertumbuhan Ekonomi Kreatif di Era Digital - Afriansyah, M.; Saputra, Joni (TIN: Terapan Informatika Nusantara, 2025)
The development of digital technology in recent years has driven global economic transformation and contributed to the emergence of the creative economy, which relies on human creativity and innovation. The animation industry, as part of the creative economy, has experienced significant growth through digital microstock platforms such as Adobe Stock, Envato Elements, and Shutterstock. This study aims to examine the role of the animation microstock industry in supporting the growth of the creative economy in Mataram City, West Nusa Tenggara. A descriptive qualitative approach was used, with data collected through observation, in-depth interviews, literature review, and documentation. Findings show that although many students and graduates in Mataram possess digital animation skills, there remain limitations in terms of access to global markets and information about microstock opportunities. However, there is strong potential in terms of technical ability, access to equipment, and a growing spirit of digital entrepreneurship. Animation microstock provides opportunities for passive income and supports independent digital creative work. With the right strategies—such as production capacity improvement, market expansion, and social media utilization—local creative actors can take advantage of these opportunities. The development of the animation microstock industry in West Nusa Tenggara holds great potential for job creation, strengthening local competitiveness, and supporting inclusive and sustainable digital economic growth.